The relationship between language proficiency and attentional control in Cantonese-English bilingual children: evidence from Simon, Simon switching, and working memory tasks - Tse, Chi-Shing; Altarriba, Jeanette (Frontiers in Psychology, 2014)
By administering Simon, Simon switching, and operation-span working memory tasks to Cantonese-English bilingual children who varied in their first-language (L1, Cantonese) and second-language (L2, English) proficiencies, as quantified by standardized vocabulary test performance, the current study examined the effects of L1 and L2 proficiency on attentional control performance. Apart from mean performance, we conducted ex-Gaussian analyses to capture the modal and positive-tail components of participants’ reaction time distributions in the Simon task. Bilinguals’ L2 proficiency was associated with higher scores in the operation span task, and a shift of reaction time distributions in incongruent trials, relative to congruent trials (Simon effect in µ), and the tail size of reaction time distributions (τ) regardless of trial types. Bilinguals’ L1 proficiency, which was strongly associated with participants’ age, showed similar results, except that it was not associated with the Simon effect in µ. In contrast, neither bilinguals’ L1 nor L2 proficiency modulated the global switch cost or local switch cost in the Simon switching task. After taking into account potential cognitive maturation by partialling out the participants’ age, only (a) scores in the working memory task and (b) RT in incongruent trials and (c) Simon effect in µ in the Simon task could still be predicted by bilinguals’ L2 proficiency. Overall, the current findings suggest that bilingual children’s L2 proficiency was associated with their conflict resolution and working memory capacity, but not goal maintenance or task-set switching, when they performed the cognitive tasks that demanded attentional control. This was not entirely consistent with the findings of college-age bilinguals reported in previous studies.